2016
DOI: 10.3390/ijerph13050510
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Determine Metal Accumulation in Agricultural Soils in the Severely Human-Coupled Ecosystem?

Abstract: Agricultural soil is typically an important component of urban ecosystems, contributing directly or indirectly to the general quality of human life. To understand which factors influence metal accumulation in agricultural soils in urban ecosystems is becoming increasingly important. Land use, soil type and urbanization indicators all account for considerable differences in metal accumulation in agricultural soils, and the interactions between these factors on metal concentrations were also examined. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Hg pristine concentrations vary between 0.08 and 0.4 mg kg -1 (Issaro et al, 2009), indicating mercury emissions from anthropogenic sources in the studied area. Results of comparisons of the obtained results with other published results for mercury (Table 2) indicate that mercury contents in Serbian river and lakes are higher that the levels measured in topsoil in Armenia Tepanosyan et al (2016) and river sediment from Spain (Roig et al, 2011), but roughly similar to measured values in soil from China (Xu et al, 2016), river sediments from Ghana (Oppong et al, 2010), Sava river (Milačič et al 2010) and Tisa river (Sakan et al 2012). The sediments mercury contents measured in this study area, however, lower than those found in soil from sewage irrigation area of northwest China .…”
Section: Mercury Arsenic and Selenium Content In Sedimentsupporting
confidence: 76%
“…Hg pristine concentrations vary between 0.08 and 0.4 mg kg -1 (Issaro et al, 2009), indicating mercury emissions from anthropogenic sources in the studied area. Results of comparisons of the obtained results with other published results for mercury (Table 2) indicate that mercury contents in Serbian river and lakes are higher that the levels measured in topsoil in Armenia Tepanosyan et al (2016) and river sediment from Spain (Roig et al, 2011), but roughly similar to measured values in soil from China (Xu et al, 2016), river sediments from Ghana (Oppong et al, 2010), Sava river (Milačič et al 2010) and Tisa river (Sakan et al 2012). The sediments mercury contents measured in this study area, however, lower than those found in soil from sewage irrigation area of northwest China .…”
Section: Mercury Arsenic and Selenium Content In Sedimentsupporting
confidence: 76%
“…Partition between available and total metal concentrations, and forms of metals in soils, are decisive respecting the accumulation in beetles and also in other organisms (Ignatowicz 2017). Additionally, other soil parameters such as soil pH, loam content, and hydrological conditions also influence the migration and uptake of metals considerably (Rakesh Sharma and Raju 2013; Xu et al 2016b). In addition, ground beetle species and their specific inherent characteristics determine the accumulation pattern significantly (Avgın and Luff 2010; Butovsky 2011).…”
Section: Discussionmentioning
confidence: 99%